Fair Access to Marine Genetic Resources in the Biodiversity Beyond National Jurisdiction Regime: A Constitutional Perspective on Indonesia’s State Obligations - Cut Yusi Ratu Aulia; Deni Kurniawan; Meisyah Rachyan; Rudi Natamihardja; Rafika Rizky Aulia Rahman (Universitas Islam Negeri Raden Intan Lampung, 2026)
Inequality in access to Marine Genetic Resources (MGRs) in Areas Beyond National Jurisdiction (ABNJ) remains a major challenge in the international law of the sea, particularly for developing countries with limited technological and research capacity. This issue is closely related to the absence of an effective benefit-sharing regime under UNCLOS, which has historically favored technologically advanced countries. This study analyzes the role of the Biodiversity Beyond National Jurisdiction (BBNJ) Agreement in addressing structural inequalities in access to and utilization of MGRs and examines its strategic implications for Indonesia. The study employs a normative legal research method, using statutory and conceptual approaches, through analysis of international legal instruments, scholarly literature, and state practices concerning mechanisms for access to and benefit-sharing of marine genetic resources. The findings indicate that the dominance of developed countries in marine scientific research and ownership of MGR-based patents persists due to disparities in technology, infrastructure, and research capacity. These conditions have implications for the realization of the constitutional rights of Indonesian citizens as guaranteed under Article 33(3) and Article 28H(1) of the 1945 Constitution, particularly regarding the utilization of natural resources, access to scientific and technological advancement, and the right to a clean and healthy environment. The BBNJ Agreement introduces normative developments through provisions on access and benefit-sharing, including technology transfer and capacity-building measures as forms of non-monetary benefits. This study concludes that Indonesia should strengthen its domestic regulatory framework, enhance marine research capacity, and optimize international cooperation to promote equitable benefit-sharing and reinforce environmental justice in implementing the BBNJ regime.